Penerapan model Pembelajaran Problem Based Learning (PBL) Berbantuan Media Flipbook Lebah untuk Meningkatkan Numerasi Anak Usia Dini - Hendiarni, Mediar; Wijayanti, Emi; Nurfaida, Anik; Sudarmiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the numeracy skills of early childhood children through the implementation of the "Lebah" digital flipbook media based on Problem-Based Learning (PBL) in Group A of Al Kautsar Bakti 2 Kindergarten, Madiun. The background of this study is based on initial findings that children's numeracy skills are still low, characterized by difficulties recognizing numbers, counting, matching quantities, and solving simple numerical problems. This condition is caused by numeracy learning that is still conventional, teacher-centered, and lacks contextual and engaging learning for children. This study used the Classroom Action Research (CAR) method with the Kemmis and McTaggart model, implemented in two cycles. Each cycle included planning, implementation, observation, and reflection. The study subjects were nine children aged 4–5 years. Data were collected through observation of learning activities, assessment of numeracy performance, anecdotal notes, and documentation. The data obtained were analyzed using quantitative descriptive analysis to assess improvements in learning outcomes, and qualitative analysis to describe the process and children's engagement during learning. The results of the study showed a significant increase in children's numeracy skills, from the category of Starting to Develop in the pre-cycle to Developing Very Well in Cycle II, with 85% of children achieving the criteria of Developing According to Expectations and Developing Very Well. In addition, the use of PBL-based flipbooks was able to increase children's engagement, motivation, and the quality of the learning process in a more concrete, contextual, and meaningful way. Thus, the PBL-based "Bee" flipbook media is effective as an innovative alternative in early childhood numeracy learning.